1993
DOI: 10.1159/000243990
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NaCl Supplementation on Vasopressin Secretion and Water Excretion in Premature Infants

Abstract: The study was carried out to assess the possible involvement of excess AVP and free water retention in the development of late hyponatremia by comparing the postnatal course of plasma AVP and urinary excretion of AVP and sodium as well as creatinine, osmolar and free water clearances in premature infants with (group S) and without (group NS) NaCl supplementation. Plasma total protein and albumin concentrations were also determined. Group NS consisted of 8 infants with a birth weight of 1,150–1,730 g (mean: 1,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Similar findings were reported by others (31,33,36). In spite of a higher serum sodium content in a group of preterm neonates receiving supplementation, no difference in daily sodium urinary excretion was noted (37) and similar results were reported by Sulyok et al (38).…”
Section: Limitations Of Serum and Urine Sodium Measurements To Determ...supporting
confidence: 88%
See 1 more Smart Citation
“…Similar findings were reported by others (31,33,36). In spite of a higher serum sodium content in a group of preterm neonates receiving supplementation, no difference in daily sodium urinary excretion was noted (37) and similar results were reported by Sulyok et al (38).…”
Section: Limitations Of Serum and Urine Sodium Measurements To Determ...supporting
confidence: 88%
“…Yet, the group receiving the lower sodium intake had serum sodium measurements as low as 130 mEq/L, with no subjects in the higher intake group having values <135 mEq/L (P < 0.05). Similarly, Sulyok et al (38) found that, when compared with intake-limited infants, an ''adequate'' sodium intake had no effect on weight gain, but significantly reduced hyponatremia, defined as <130 mEq/L, in the supplemented group.…”
Section: Evidence For the Effect Of Sodium Deficiency On Preterm Neon...mentioning
confidence: 90%
“…Sulyok et al (1979b) related late hyponatremia to a tubular unresponsiveness to aldosterone rather than to any deficiency in the renin-angiotensin-aldosterone system. This suggests that late hyponatremia should be preventable by providing additional salt, although perhaps at the cost of vasopressin-mediated water retention and volume expansion (Sulyok et al, 1993).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…It has been suggested as an index of AVP activity in kidney collecting ducts [6,33]. However, the immature kidney is resistant to AVP [34,35]. Our data indicate that urinary AQP2 cannot serve as a direct marker of the renal action of AVP in newborn babies.…”
Section: Discussionmentioning
confidence: 72%